Characteristics of miRNA interaction with mRNAs of candidate genes of human cardiovascular diseases (Experimental biology, 2018)
The binding of 6271 human miRNAs with mRNAs of 74 candidate genes was studied. These genes, presumably, can be biomarkers and play a key role in the development of myocardial infarction, ischemic heart disease, arterial hypertension, atherosclerosis and metabolic syndrome and perform various functions. Among the results obtained we have selected 438 miRNA binding sites in mRNAs of these genes, taking into account binding energy, ΔG/ΔGm ratio and the length of miRNAs. The largest number of binding sites (155) is found in mRNAs of ischemic heart disease gene candidates. Only four genes had miRNA binding sites in their mRNAs with ΔG/ΔGm value equal to 100%: TPM1, GATA5, NKX2-5 and F2. GATA4, NKX2-5, TTN, LDLR and PPARGC1A genes contained the largest number of miRNA binding sites in their mRNAs among studied genes. Based on the results obtained, we can make conclusion that the expression of gene candidates of ischemic heart disease is more strongly regulated by miRNAs than the expression of gene candidates of other cardiovascular diseases described in the article. Associations of miRNAs and mRNAs of candidate genes of myocardial infarction, ischemic heart disease, arterial hypertension, atherosclerosis and metabolic syndrome development were found. The following associations of miRNAs and mRNAs of candidate genes, characterizing by free energy of interaction equal and more than -130kJ/mole, can be recommended for diagnostics of myocardial infarction, ischemic heart disease, arterial hypertension, atherosclerosis and metabolic syndrome: ACE1 and miR-3-8100-5p; ACTA2  and miR-19-44540-3p; AST1 and miR-17-40081-5p; GATA2 and miR-7-21068-3p; GATA4 and miR-1-155-3p, miR-3-8100-5p, miR-2-3313-3p, miR-16-13062-5p; GATA6 and miR-6-17815-3p; HIF1A and miR-6789-5p, miR-6-16980-5p; INSR and miR-4-11316-5p; MAPK1 and miR-17-39570-5p, miR-12-33610-3p, miR-9-20317-3p, miR-19-41910-5p; MYL4 and miR-4763-3p; NKX2-5 and miR-19-21199-3p, miR-20-22562-3p, miR-2-3313-3p, miR-1-2121-3p; PPARGC1A and miR-9-20317-3p, miR-5-15733-3p; TNNI3 and miR-2-7379-5p; TPM1 and miR-15-35627-5p;  VEGFB and miR-20-22562-3p,  miR-19-33623-3p,  miR-19-30988-5p, miR-19-21199-3p, miR-1-2121-3p; VEGFC and miR-15-32047-5p, miR-17-40081-5p, miR-2-3313-3p, miR-20-45152-5p; VLDLR and miR-9-20317-3p. It is possible to control in the blood concentrations of these associations of miRNAs and mRNAs of candidate genes, suggested for early diagnostics of cardiovascular diseases.
Keywords: miRNA; mRNA; gene candidates; myocardial infarction; ischemic heart disease; arterial hypertension; atherosclerosis; metabolic syndrome